Yagi Array of Microstrip Quarter-Wave Patch Antennas with Microstrip Lines Coupling - Juhua Liu; Yue Kang; Jie Chen; Yunliang Long (International Journal of Antennas and Propagation)
A new kind of Yagi array of quarter-wave patch antennas is presented. The Yagi array has a low profile, a wide bandwidth, and a high gain. A main beam close to endfire is produced, with a vertical polarization in the horizontal plane. A set of microstrip lines are introduced between the driven element and the first director element to enhance the coupling between them, and therefore the bandwidth could be increased and the back lobes could be suppressed. Measured results show that the Yagi array with 4 elements generates a peak gain of about 9.7 dBi, a front-to-back ratio higher than 10 dB, and a 10 dB return loss band from 4.68 GHz to 5.24 GHz, with a profile of 1.5 mm and an overall size of 80 × 100 mm2. An increase of the number of director elements would enhance the gain and have the main beam pointing closer to endfire.